The new Turkish diaspora policy: Its aims, their limits and the challenges for associations of people of Turkish origin and decision-makers in Germany - Yaşar Aydın (Stiftung Wissenschaft und Politik (SWP), 2014)
The activities of the Turkish government for people of Turkish origin in Germany are part of a political strategy aimed at strengthening the diaspora organisations. From Ankara's point of view, globalisation is forcing Turkey to reposition itself in the web of international relations and to make use of the potential of people of Turkish origin who are scattered across the world. It can therefore be expected that Turkey will continue to focus its attention on the diaspora of people of Turkish origin in Germany. German politicians are often influenced by the spectre of a "fifth column" or "Trojan horse" in their assessment of the Turkish diaspora and Ankara's diaspora policy. Here the integrative aspects of both the diaspora as a way of life and of diaspora policy are completely overlooked. Ankara's diaspora policy results not only in challenges for German foreign policy but also in opportunities for integration policy in Germany. Turkish decision-makers call on people of Turkish origin in Germany to make better use of education opportunities, to make greater effort to improve their social status and to take an active part in the life of society and the formation of public opinion. This can only be achieved by adopting modern patterns of behaviour and an open attitude. In this respect the Turkish diaspora policy complements German integration policy and efforts of people of Turkish origin to integrate. (SWP Research Paper)
Keywords: 320